Potensi Pemanfaatan Serat Selulosa sebagai Material Bahan Baku dalam Sintesis Filter Udara Non-Woven sesuai Standar TAPPI T 205 - Irwan Suriaman; Mardiyati; Jooned Hendrarsakti; Ari Darmawan Pasek (Sekolah Tinggi Teknologi Wastukancana, 2020)
Industry 4.0 era materials used by entrepreneurs should be recycled, environmentally friendly, renewable with less chemical content. Indonesia as a tropical country has a large land area with the potential to produce the largest natural fiber in the world. One opportunity that can be applied to the utilization of natural fibers in air filters that currently use dominant materials is synthetic fibers. natural fiber has the advantage because it does not contain toxic chemicals, local raw materials, and is easily produced. This research will analyze the mechanical and morphological characteristics of biological fibers that have great potential as pre-filter raw material. Analysis of mechanical properties through tensile strength testing for single fibers and morphological analysis through scanning electron microscopy (SEM). Tensile testing was the results are; palm oil has a tensile strength of 620 MPa; 998 MPa and 213 MPa flax coconut fiber. For the morphological test results from SEM analysis for ramie fiber, it looks solid without fiber holes; The fibers appear to be many small fibers bound to one another while coir fibers have many pore holes in one observed fiber.